Diversity of serine hydrolase activities of unchallenged and botrytis-infected Arabidopsis thaliana. - Kaschani, F; Gu, C; Niessen, S; Hoover, H; Cravatt, B; van der Hoorn, R (2009)
Activity-based protein profiling is a powerful method to display enzyme activities in proteomes and provides crucial information on enzyme activity rather than protein or transcript abundance. We applied activity-based protein profiling using fluorophosphonate-based probes to display the activities of Ser hydrolases in the model plant Arabidopsis thaliana. Multidimensional protein identification technology and in-gel analysis of fluorophosphonate-labeled leaf extracts revealed over 50 Ser hydrolases, including dozens of proteases, esterases, and lipases, representing over 10 different enzyme families. Except for some well characterized Ser hydrolases like subtilases TPP2 and ARA12, prolyl oligopeptidase acylamino acid-releasing enzyme, serine carboxypeptidase-like SNG1 and BRS1, carboxylesterase-like CXE12, methylesterases MES2 and MES3, and S-formylglutathione hydrolase, the majority of these serine hydrolases have not been described before. We studied transiently expressed SNG1 and investigated plants infected with the fungal pathogen Botrytis cinerea. Besides the down-regulation of several Arabidopsis Ser hydrolase activities during Botrytis infection, we detected the activities of Botrytis-derived cutinases and lipases, which are thought to contribute to pathogenicity.